Potent in vitro antiviral activity of the extract of Echinacea angustifolia against bovine herpesvirus 1 - Renata Pierobom Gressler; Paulo Ricardo Centeno Rodrigues; Renata Nobre da Fonseca; Geferson Fischer; Marcelo de Lima; Silvia de Oliveira Hübner (Ciência Rural)
ABSTRACT: Echinacea angustifolia is a perennial plant that has been traditionally used to treat various microbial diseases. This study evaluated the in vitro antiviral properties of an ethanolic extract of E. angustifolia against bovine alphaherpesvirus 1 (BoHV-1). BoHV-1 infection is associated with respiratory, reproductive and neurological disease in cattle, resulting in major economic losses. When cells were treated with E. angustifolia extract at a non-cytotoxic concentration at different times (3, 6 or 24 hours) before BoHV-1 inoculation, no viral detection was possible after 72h, while in untreated cells the virus reached a titer of 105.5TCID50 /25µl (median). Incubating the extract with BoHV-1 24 hours before cell inoculation did not result in loss of viral infectivity. Cells infected with 103 TCID50 of BoHV-1 and not treated with E. angustifolia showed an average of 45.8% viability after 48 hours of infection, while 91.1% remained viable when treated 6 hours after or 84.1% 24 hours after infection, demonstrating a significant reduction in the cytopathic effect. In addition, E. angustifolia significantly reduced the relative mRNA expression of the antiviral cytokines IFNα and IFNβ in the treated cells, suggesting that the antiviral activity is not due to immunomodulation. The obtained data indicated that the ethanolic extract of E. angustifolia may directly interfere with virus attachment, entry, and/or egress from infected cells. Taken together, the presented data emphasized the promising antiviral activity of E. angustifolia against BoHV-1.